Reduction of automatically maintained self-injurious behavior - Arsić, Bojana; Gajić, Anja; Vidojković, Sara; Maćešić-Petrović, Dragana; Bašić, Aleksandra (Universitas Majalengka, 2022)
Self-injurious behaviour (SIB) is highly prevalent in the population of children with autism spectrum disorders (ASD), with one-third of the sample engaging in it and in most cases, SIB is automatically reinforced. Therefore, the aim of this paper is to examine the effectiveness of the noncontingent matched stimulation (NCRMS) procedure in combination with wearing wrist weights on reducing automatically reinforced SIB in an 11-year-old participant with ASD and epilepsy who exhibited high rates of head and chin SIB, as well as to examine the effectiveness of the isolated application of those two procedures. NCRMS procedure alone leads to immediate SIB reduction for head SIB of 75% on average while for chin SIB leads to 90% of reduction on average. Wrist weight wearing alone was not as efficient, since it led to head SIB reduction of 31% on average and chin SIB reduction with an average of 51%. A combination of those two procedures was proven to be successful in reducing SIB, with the average success rate of 93% for head SIB and 98% for chin SIB. We believe that wearing wrist weights only increased response effort for engaging in problem behaviour, while the NCRMS procedure matched the reinforcing properties of SIB and consequently reduced it. It is important to examine the practical aspect of wearing massagers outside of the house because it can lead to attracting negative attention from others and future research might examine the acceptability of NCRMS procedure implementation that involves the use of certain objects that are not socially acceptable for public use.